Translational switch for long‐term maintenance of synaptic plasticity - Naveed Aslam; Yoshi Kubota; David Wells; Harel Z Shouval (Molecular Systems Biology)
Abstract Memory can last a lifetime, yet synaptic contacts that contribute to the storage of memory are composed of proteins that have much shorter lifetimes. A physiological model of memory formation, long‐term potentiation (LTP), has a late protein‐synthesis‐dependent phase (L‐LTP) that can last for many hours in slices or even for days in vivo. Could the activity‐dependent synthesis of new proteins account for the persistence of L‐LTP and memory? Here, we examine the proposal that a self‐sustaining regulation of translation can form a bistable switch that can persistently regulate the on‐site synthesis of plasticity‐related proteins. We show that an αCaMKII–CPEB1 molecular pair can operate as a bistable switch. Our results imply that L‐LTP should produce an increase in the total amount of αCaMKII at potentiated synapses. This study also proposes an explanation for why the application of protein synthesis and αCaMKII inhibitors at the induction and maintenance phases of L‐LTP result in very different outcomes.